2018
DOI: 10.1016/j.bbalip.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Intake of stigmasterol and β-sitosterol alters lipid metabolism and alleviates NAFLD in mice fed a high-fat western-style diet

Abstract: Objective: To investigate and compare the effects of two common dietary phytosterols, stigmasterol and β-sitosterol, in altering lipid metabolism and attenuating nonalcoholic fatty liver disease (NAFLD). Methods: Stigmasterol and β-sitosterol were administered to mice at 0.4% in a high-fat western-style diet (HFWD) for 17 weeks. Results: Stigmasterol and β-sitosterol significantly ameliorated HFWD-induced fatty liver and metabolic abnormalities, including elevated levels of hepatic total lipids, triacylgly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 46 publications
7
86
0
Order By: Relevance
“…The ability of the rat IM to make SF from GRP changes with the length of dietary exposure to broccoli [11]. Whereas it is known that broccoli consumption also affects the ability of many human IM to produce SF, it is well established that there is significant variation among individuals in the response of their IM to broccoli consumption [34]. For example, this might be due to absence of certain microbiota in some individuals, microbiota that enhance or disrupt SF formation and absorption.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the rat IM to make SF from GRP changes with the length of dietary exposure to broccoli [11]. Whereas it is known that broccoli consumption also affects the ability of many human IM to produce SF, it is well established that there is significant variation among individuals in the response of their IM to broccoli consumption [34]. For example, this might be due to absence of certain microbiota in some individuals, microbiota that enhance or disrupt SF formation and absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Constant consumption of stigmasterol can reduce blood LDL cholesterol by 8%-10%, which lowers the risk of cardiovascular disease [9]. Further, stigmasterol inhibits the accumulation of fatty acids [10]. In plant seeds, stigmasterol promotes cell proliferation, maturation, and germination [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that stigmasterol is related to almost the same genes as C09367, excepting the AR gene. Mouse experiments demonstrated that stigmasterol prevented the HFWD-induced elevation of some di-and triacylglycerol species, decreased serum levels of ceramides, inhibited intestinal absorption of cholesterol and plant sterol, and suppressed hepatic cholesterol [35,36]. Therefore, these key ingredients can achieve a good effect on CHD by lowering cholesterol, inhibiting platelet aggregation, suppressing in ammatory response and relieving the pain.…”
Section: Discussionmentioning
confidence: 99%